Analysis of Offense Sexual Abuse on The Psychological Effects of Victims - Febriansyah, Ferry Irawan; Ikhwan, Afiful; Agiyanto, Ucuk; Saputri, Pretty Desya (NAJAHA, 2023)
The population level of citizens must be balanced with the high level of welfare of the Indonesian population. Every citizen has the right to obtain it by allowing it to grow and develop optimally, physically, mentally, socially and as a personality. One of the efforts is to protect against violence, in this case, sexual violence. This study aims to reveal the impact caused by victims of sexual abuse. The results of this study explain that the psychological impact of sexual harassment is quite a lot, such as somatization, nervous pain, chronic pain, changes in sexual behaviour, schooling, learning problems, and problems including the use of illegal drugs, self-harm, cruelty to animals, human crime. Grown up and committed suicide. Therefore, the state's role is to provide legal protection to create a sense of security and legal guarantees for the obscenity that befalls them.